Polymorphism of CYP1A1 (Ile462Val) Gene Related to Uterine Myoma in Malays Ethnicity of South Sumatera - Bella Ria Astuti; Ferry Yusrizal; Legiran Legiran (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2020)
ABSTRACTASSOCIATION BETWEEN CYP1A1 (Ile462Val) GENE POLYMORPHISM AND OCCURANTE OF UTERINE MYOMA IN MALAYS POPULATION IN SOUTH SUMATERA.Bella Ria Astuti1, Ferry Yusrizal2 dan Legiran3Biomedical Science Program, Faculty of Medicine, University Sriwijaya          Background :  Uterine myoma is a tumor in the myometrium. Uterine myoma is a disease associated with interactions between genes, hormones, growth factors, cytokines, and the environment. Myoma has never been found before menarche, whereas after menopause only about 10% of myomas still grow. In general the incidence of uterine myoma is predicted to reach 20-30% in women over 35 years. In Indonesia myoma was found 2.39% - 11.7%. Uterine myomas can cause various symptoms including menometroragia, pelvic pain, spontaneous abortion and infertility. that the growth and development of uterine myomas depends on estrogen. Cytochrome CYP450 system is a group of enzymes involved in biosynthesis of steroid hormones and metabolic activation of carcinogens. CYP1A1 is one of three members of the CYP1 family that plays a role in the metabolism of large numbers of xenobiotics. The purpose of this study is to analyze the relationship of CYP1A1 (Ile462Val) gene polymorphism with the incidence of uterine myoma in ethnic Malays in South Sumatra.          Methods : This study is an observational analytic study with a case control. This research was conducted in February 2019 in the laboratory of molecular Biology, Faculty of Medicine, Sriwijaya University. Test the statistics using the chi square test. The study sample used blood samples taken in 70 samples consisting of 35 case samples and 35 control cases. CYP1A1 (Ile462Val) gene polymorphism using the method PCR-RFLP.          Results : There is a relationship between Polymorphism between genotypes and gene alleles CYP1A1 (Ile462Val) with the incidence of uterine myoma in ethnic Malays in South Sumatra. Key words      :  Polymorphism, Gene CYP1A1 (Ile462Val), Uterine leiomyoma.Citations          :  63 (2001-2015)